CNG-Diesel Dual Fuel Controlling Concept for Common Rail Diesel - Ismail, Muammar Mukhsin; Mohd Ali, Mas Fawzi; Zulkifli, Abd Fathul Hakim; Osman, Shahrul Azmir (International Journal of Integrated Engineering, 2018)
Compressed Natural Gas (CNG) is gaining interest as a clean fossil fuel alternative in a diesel dual fuel system. The dual fuel system is proven to provide benefits in terms of fuel consumption and exhaust emission. This article briefly describes a concept of controlling strategy of a CNG-diesel dual fuel system for a common rail diesel engine. A lower diesel common rail pressure was emulated to reduce the diesel fuel quantity, then substitute it with an equivalent CNG fuel quantity. The tuning process is vital to ensure a comparable performance. It requires measurement of lambda values and tuning of both diesel and CNG set values in their respective look-up tables for the whole engine operation. Test results showed that the lambda values are between 1.5 and 3.0, depending on the load demand indicated by the accelerator pedal positions. This concept is relatively easy to be implemented, but it may cause poor combustion and emission quality due to poor diesel fuel atomization at lower injection pressure. However, an optimum performance and emission could be achieved by scrutinizing the diesel fuel reduction and CNG fuel substitution.